Ambulance attendance for substance and/or alcohol use in a pandemic: Interrupted time series analysis of incidents. (1st March 2022) - Mason, Rachael; Roberts, Amanda; Spaight, Robert; Shaw, Debbie; Whitley, Gregory Adam; Hogue, Todd E.; Siriwardena, Aloysius Niroshan; Rogers, Jim; Law, Graham R.
Abstract: Introduction: The ambulance attendance for substance and/or alcohol use in a pandemic (ASAP) study explores incidents during the COVID‐19 lockdown in the East Midlands region of the United Kingdom (23 March–4 July 2020). Method: Retrospective cross‐sectional count per day of ambulance attendances from the East Midlands Ambulance Service Trust. Ambulance attendances relating to alcohol or other drug use in the year prior, during lockdown and weeks following, were examined using interrupted time series analysis by patient demographics and geographical location. Results: A total of 36 104 records were identified (53.7% male, 84.5% ethnicity classified as White, mean age 38.4 years). A significant drop in the number of attendances per day at the start of lockdown (−25.24, confidence interval − 38.16, −12.32) was observed, followed by a gradual increase during the ongoing lockdown period (0.36, confidence interval 0.23, 0.46). Similar patterns were found across genders, age groups 16–64 and urban/rural locations. Discussion and Conclusion: The pattern of ambulance attendances for alcohol or other drug use changed during the COVID‐19 lockdown period. Lockdown significantly affected the use of ambulances for incidents involving alcohol or other drug use, impacting on health‐care services. Further research into hazardous use of alcohol or other drugs during the lockdown periods is needed to inform policy, planning and public health initiatives.